Beta-human chorionic gonadotropin, carbohydrate antigen 19-9, cancer antigen 125, and carcinoembryonic antigen as prognostic and predictive biological markers in bladder cancer - Yuk, Hyeong Dong; Han, Jang Hee; Jeong, Seung-Hwan; Jeong, Chang Wook; Kwak, Cheol; Ku, Ja Hyeon (Frontiers in Oncology, 2024)
IntroductionWe evaluated the prognostic potential of the Beta-human chorionic gonadotropin (β-hCG), Carbohydrate Antigen 19-9 (CA19-9), Cancer Antigen 125 (CA125), and Carcinoembryonic Antigen (CEA) tumor markers for bladder cancer.MethodsWe analyzed the records of 369 patients who underwent radical cystectomy for urothelial cancer (UC) between October 2012 until December 2019. Levels of CA19-9, CA125, CEA, and β-hCG before radical cystectomy were measured in all patient samples, and serum biomarker cutoff values were used as normal and elevated values.Results and discussionThe proportion of abnormal β-hCG (P<0.001), CA19-9 (P<0.001), and CA125 (P=0.033) was significantly higher in locally advanced bladder UC than in organ-confined bladder UC. In patients with preoperative β-hCG and CA125 abnormality, there was poor prognosis of recurrence-free survival (RFS)(P=0.003, P=0.042) and overall survival (OS) (P=0.003, P=0.002). Using the Cox multivariate regression analysis, both β-hCG (HR: 3.88, 95% CI: 1.43–10.25) and CA125 (HR: 6.21, 95% CI: 1.34–32.16) were found to be significant independent factors for predicting OS and RFS. In addition, patients with a high number of increased tumor markers showed significantly worse OS ((P<0.001) and RFS (P=0.002) than patients with a low number of increased tumor markers. In conclusion, serum β-hCG and CA125 levels could potentially be used for UC prognosis in patients undergoing radical cystectomy. To assess their usefulness in evaluating long-term recurrence and survival, further treatment responses and large-scale additional studies are needed.